Basic Principles and Stages of Betting in the Face Area - Allaberdiyeva Zulfizar Xayrullayevna; Tastanova Gulchexra Eshtayevna; Tulemetov Sabrjan Kalikovich (Zien Journals, 2023)
This academic paper explores the fundamental principles and critical importance of suturing techniques in the context of facial and jaw surgeries. The face and jaw area present unique challenges due to their aesthetic significance and functional complexities. The paper delves into the various suturing methods employed in these delicate regions, emphasizing the significance of precise and meticulous techniques to achieve optimal wound closure and minimize complications
Keywords: Implants; surgery; surgical instruments